PRINCIPALS’ APPLICATION OF EDUCATION MANAGEMENT INFORMATION SYSTEM IN ADMINISTRATION OF PUBLIC SECONDARY SCHOOLS IN ANAMBRA STATE (UNIZIK Journal of Educational Management and Policy, 2024)
The study investigated principals’ application of education management information system in administration of public secondary schools in Anambra State. Three research questions guided the study and three null hypotheses were tested at 0.05 level of significance. The descriptive survey research design was adopted for the study. The population of the study comprised 268 principals in public secondary schools in Anambra State. A sample size of 134 principals was draw for the study using sample random sampling technique. A researcher-developed questionnaire titled ‘Principals’ Application of Education Management Information System in School Administration Questionnaire (PAEMISSAQ)’ was used for data collection. The instrument was validated by three experts and subjected to the test of internal consistency of instrument using Cronbach alpha which yielded a coefficient value of 0.81. Data analysis was done using Mean and standard deviation to answer the research questions, while t-test to test the hypotheses. The findings of the study revealed among others that principals do not apply education management information system in most areas of record management, students and staff personnel administration in public secondary schools in Anambra State. It was also found that there is no significant difference in the mean ratings of male and female principals on the application of education management information system in all aspects of administration in public secondary schools in Anambra State. Based on the findings, it was recommended among others that the Ministry of Education should organize annual training programme for principals to enable them upgrade their skills and knowledge on the application of EMIS in record management.
Keywords: Principals, Application, Education Management, Information System, School Administration